THE EFFECT OF FLIPPED LEARNING 3.0 AND SELF-REGULATED LEARNING ON TWELFTH GRADE STUDENTS SPEAKING PERFORMANCE - Dasa, Agung Krsna Lila; Adnyani, Luh Diah Surya; Budiarta, Luh Gd. Rahayu (Universitas Pendidikan Ganesha, 2021)
This study aimed to investigate the effect of flipped learning (FL) 3.0 and self-regulated learning (SRL) on the speaking performance of twelfth-grade students in Buleleng. This study was experimental study that focused on Quasi-Experimental design. The sample was 63 students that classified into the control and experimental class through random sampling to the intact groups. Data were collected from the speaking performance score and questionnaires. The results showed that significant difference of students speaking performance taught by FL 3.0 and conventional method was 0.048, means that it was significant. Students' speaking performance difference who has low and high SRL was 0.568, means that it was not significant. The interaction effect of FL 3.0 and SRL was 0.790, means that they had no interaction effect. FL 3.0 could be used in teaching speaking because it had significant effect on students' speaking performance even though the students have high or low SRL.